APOBEC in breast cancer: a dual player in tumor evolution and therapeutic response - Lu, Haiqi; Lu, Zelin; Wang, Yufei; Chen, Miaoqin; Li, Guangliang; Wang, Xian (Frontiers in Molecular Biosciences, 2025)
The APOBEC (Apolipoprotein B mRNA-editing enzyme, catalytic polypeptide-like) family of cytidine deaminases has emerged as pivotal a contributor to genomic instability and adaptive immunity through DNA/RNA editing. Accumulating evidence underscores their dual role in breast carcinogenesis—driving tumor heterogeneity via mutagenesis while simultaneously shaping immunogenic landscapes. This review synthesizes current insights into APOBEC-mediated molecular mechanisms, focusing on their clinical implications across breast cancer subtypes. Notably, APOBEC-driven mutagenesis correlates with elevated tumor mutational burden (TMB), replication stress vulnerability, and immune checkpoint inhibitor (ICI) responsiveness. Paradoxically, these mutations also accelerate endocrine therapy resistance and subclonal diversification. We propose APOBEC mutational signatures as predictive biomarkers for ICI efficacy and discuss therapeutic strategies leveraging APOBEC activity, including ATR inhibition and hypermutagenic immunotherapy. Harnessing APOBEC’s duality—balancing its pro-immunogenic effects against genomic chaos—may redefine precision oncology in breast cancer.